REPAIR UTTERANCES USED BY BART AND HOMER IN THE SIMPSON - Veronika Listi Ferdini Damopolii (JELLT (Journal of English Language and Literature Teaching), 2021)
The research explores Repair Utterances Used suggested by McManis, et al (1988). The goals of the of the analysis are to know the repairs used by the speaker and to find out speaker meaning or intention meaning by using those repairs. The research uses a qualitative descriptive method to describe the data. The data analyzed by using pragmatic approach to ease the writer identify the speaker meaning. The speaker uses repairs: Uh, Umm, Ehm, Uh-uh, and Uh. The speakers use those repair to show sometimes there are speech errors or unclear utterances made by the speaker and after that the speaker immediately realizes it and will correct his mistake, but it is also possible if the listener asks for correction or clarification by asking the speaker. However, the use of repair in conversation has a purpose and the reasons why they do repairs to their interlocutor in conversation, such as because to emphasize speaker previous explanation, to clarify something because the speaker doesn't understand what is talking about, to say something wrong and repair it, to ask clarification of unclear statement, and to clarify less specific explanation.